CDR 2018
DOI: 10.20517/cdr.2017.01
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of mitomycin C resistance in human bladder cancer T24 cells by knocking-down ras oncogene

Abstract: Aim: Mitomycin C (MMC) is a commonly used as intravesical treatment for superficial bladder cancer. However, its role in combination with ras inhibition has not been investigated. The aim of this study was to explore the role of ras in MMCinduced apoptosis in T24 bladder cancer cells and to determine the efficacy of combination therapy in vitro . Methods:We measured the effects of various doses of MMC on apoptosis induction as well as on ras, ERK and Ki-67 protein expression by T24 cell line using immunocytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The activated Ras/Raf/ERK-signaling pathway creates a robust proliferative stimulus that leads to uncontrolled cell division [25][26]. In a previous study [18],…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The activated Ras/Raf/ERK-signaling pathway creates a robust proliferative stimulus that leads to uncontrolled cell division [25][26]. In a previous study [18],…”
Section: Discussionmentioning
confidence: 96%
“…In our previous study [18], we used MMC in low and high concentrations (up to 100 μg/ml) in combination with two different concentrations of Ras siRNA, and we found that Ras siRNA sensitized T24 cells to apoptosis induced by…”
Section: Conclusion Of Synergism Between Drug Combinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [111,112], in the case of bladder cancer, have shown that the treatment with mitomicyn-C decreased the recurrence rate after 10 years by 40%.…”
Section: Chemotherapymentioning
confidence: 99%
“…Treatment often induces repair mechanism in the cell. The paper by Sharaf Eldin et al [17] describes the role of apoptosis in resistance to another alkylating drug, but surprisingly RAS expression is also involved in resistance. They describe a novel approach to reverse resistance by the use of siRNA, which suppresses the survival pathway in which RAS plays a role.…”
Section: What Is Special In the First Issue?mentioning
confidence: 99%